2019
DOI: 10.1158/1055-9965.epi-18-0812
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Time to Treatment to Achieve Durable Biochemical Disease Control after Surgery in Prostate Cancer: A Multi-Institutional Cohort Study

Abstract: Background: The impact of treatment delays on prostate cancer-specific outcomes remains ill-defined. This study investigates the effect of time to treatment on biochemical disease control after prostatectomy. Methods: This retrospective study includes 1,807 patients who received a prostatectomy as a primary treatment at two large tertiary referral centers from 1987 to 2015. Multivariate cox model with restricted cubic spline was used to identify optimal time to receive treatment and estimate the risk of bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…This perception seems to coincide with available literature reports describing treatment delay >6 months based on risk category [20,21]. However, a recent study suggested that delayed prostatectomy was not associated with adverse oncologic outcomes for intermediate or high risk disease [20,21]. A sum of 94.4% of respondents indicated they cancelled more than half of low and favorable intermediate risk prostate surgeries, 72% more than half of unfavorable intermediate risk cases, and 56.2% more than half of high risk cases (Figure 1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This perception seems to coincide with available literature reports describing treatment delay >6 months based on risk category [20,21]. However, a recent study suggested that delayed prostatectomy was not associated with adverse oncologic outcomes for intermediate or high risk disease [20,21]. A sum of 94.4% of respondents indicated they cancelled more than half of low and favorable intermediate risk prostate surgeries, 72% more than half of unfavorable intermediate risk cases, and 56.2% more than half of high risk cases (Figure 1).…”
Section: Discussionsupporting
confidence: 89%
“…Many felt that there could be disease progression with delays for unfavorable intermediate risk and high risk cases (Figures 2A-2B). This perception seems to coincide with available literature reports describing treatment delay >6 months based on risk category [20,21]. However, a recent study suggested that delayed prostatectomy was not associated with adverse oncologic outcomes for intermediate or high risk disease [20,21].…”
Section: Discussionsupporting
confidence: 81%
“…To the best of our knowledge, this is the largest study specifically 514 379 276 207 153 98 58 35 28 14 3 0 464 1198 872 669 487 355 215 130 82 45 19 5 0 1051 3574 2554 1948 1483 1064 697 400 237 124 53 9 0 3154 9526 7021 5414 4028 2844 1803 1001 571 314 134 36 0 8422 11 653 8741 6829 5121 3546 2298 1289 698 399 179 47 0 10 evaluating the impact of surgical delay on the pathological outcomes of high-risk prostate cancers in the literature. 4,17,19,20 Previous studies 4, 17,19,[21][22][23] evaluating associations of SDT with postprostatectomy outcomes have 2 common features. First, they included patients with intermediate-risk and low-risk cancer, which might contaminate the findings for high-risk cancers.…”
Section: Discussionmentioning
confidence: 99%
“…17,[23][24][25] Second, previous studies also had to compromise by categorizing SDT into only 2 or 3 groups with large time intervals because of limited sample sizes. 4,17,21,25 For example, both Gupta et al 17 these patients. 28,29 For newly diagnosed high-risk and very-high-risk prostate cancer, the current evidence is less convincing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation